2009
DOI: 10.1002/pssc.200881510
|View full text |Cite
|
Sign up to set email alerts
|

InAlAs/InAs/InGaAs pseudomorphic high electron mobility transistors exhibiting ultra‐fast optical response

Abstract: High electron mobility transistors with a pseudomorphically strained InAs channel (InAs‐PHEMTs) have superior electron‐transport properties and high electron density, which are due to a large conduction‐band discontinuity. In this work, we demonstrate that InAs‐PHEMTs have an additional property: they exhibit an ultra‐fast optical response with a time‐constant of 3.5 × 10–11 s. By irradiating the optical signal onto the InAs‐PHEMTs, hole‐electron pairs are created in the channel layer. Holes accumulated in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 12 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…6) In addition, we have demonstrated that InAs-PHEMT can operate as not only a high-speed transistor but also an ultra high-speed optical receiver. 7) In this work, we show the dependence of optical response on drain-to-source voltage (V DS ) for InAs-PHEMTs and clarify the physical mechanism for the response time. To physically understand the optical response, we estimated the minority carrier lifetime using the Auger recombination theory.…”
Section: Introductionmentioning
confidence: 89%
“…6) In addition, we have demonstrated that InAs-PHEMT can operate as not only a high-speed transistor but also an ultra high-speed optical receiver. 7) In this work, we show the dependence of optical response on drain-to-source voltage (V DS ) for InAs-PHEMTs and clarify the physical mechanism for the response time. To physically understand the optical response, we estimated the minority carrier lifetime using the Auger recombination theory.…”
Section: Introductionmentioning
confidence: 89%
“…We have been studying the physical properties of a phenomenon expressed in high electron mobility transistors (HEMTs) of the kind used in ultra-highspeed field effect transistors (FETs) [3][4][5]. Our previous research on inhibitors of carrier transport led us to propose fusing a high-speed device with a photo-responsive device [6].…”
Section: Introductionmentioning
confidence: 99%
“…A current-gain cut-off frequency (f t ) of 628 GHz [2] and a maximum oscillation frequency (f max ) of 1.2 THz have been reported [1]. In our previous study regarding the effect of optical irradiation on InAlAs/InGaAs HEMT characteristics, we demonstrated that a shift of threshold voltage (V TH ) in InAlAs/InGaAs HEMTs is caused by the change in the Fermi level due to the holes accumulated in the source region [3,4]. The carrier lifetime of accumulated holes is dominated by Auger recombination of holes in the two-dimensional electron gas (2DEG) [3][4][5].…”
mentioning
confidence: 95%
“…Furthermore, we have shown that InAlAs/InGaAs HEMTs have a high responsivity when they are used as optical receivers [5]. Recently, we have demonstrated that InAs-PHEMTs can operate as not only high-speed transistors but as ultra-high speed optical receivers [3][4][5][6].…”
mentioning
confidence: 97%
See 1 more Smart Citation